Epidural Versus Opioid Analgesia for Pain Relief In Labour : A Comperative Study (Journal of Chittagong Medical College Teachers' Association, 2018)
Backgroud : Pain management is an universal concern for women during labour. Ideal labour analgesia should effectively reduce the pain and have minimal adverse effects on the fetus and progress of labour. Materials and methods : The present cross sectional comparative study was carried out in the Department of Obstetrics and Gynecology, Chittagong Medical College Hospital (CMC&H) between January 2014 and July 2014 to compare the efficacy and safety between epidural analgesia and opioid analgesia on nulliparous women in labour. In this study, study population were Pregnant women with labour pain admitted in the Department of Obstetrics and Gynaecology, CMC&H. Samples were selected following inclusion and exclusion criteria. Then randomization was done to divide them in groups, group A & B each having 40 patient. Group A received epidural analgesia at the L3-4 interspace with 0.125% Bupivacaine 10 ml and Fentanyl 50 mg & group B received opioid analgesia (Inj. Pethidine and Phenargon). Then the subjects were followed up and outcome were recorded in a preformed data collection sheet. All data were analyzed by computer based software SPSS version 15. Quantitative data was analyzed by Student’s t- test. Categorical variables were analyzed by Chi square (c2) test & Fisher’s Exact Test. Results : Statistical significance was set at P value less than